(3GdeZfj TQM GdehLR aj GdWHs - (3SOjO GdOjf GdcGRQhfj, cGf MjG (B745(3g`s ((3LGeY GdeSdhJ (B((3OeTb(B)s)
(3ChdgG (B:s
(3GdMeO ddg GdPj CHOY HbOQJg LhGgQ YbdjI eLQOIhdeG QCjJ GdeNJUQ GdPj Cdag GdMcje GdaGVd hGdWHjH GdeGgQ GHf CHj GdMRe GdbQTj GdeYQha HGHf GdfajS hSeGg HGdehLRCQOJ JhVjM HYV ehGVYghSejJg HcJGH GdeZfj aj TQM GdehLRs
(3BNQgG (B:s
(3hCbhd hCfG SOjO GdcGRQhfj gPG BNQ TQM GdehLR hbO LeYJ ajg NdGUI cdGe GdMceGA GdChdjf hGdBNQjf ef GdEeGe GdebOe CHbQGW hLGdjfhS hMfjf hGdQGRj hef TQhM GdbGfhfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: 1 / 753s
(3cTa GdXfhf(B: 2 / 1900s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdWHs